L’ergastolo e la dignità umana: un caso lampante di disattuazione della costituzione e degli obblighi internazionali assunti dallo Stato Italiano - Freitas, Janaína Thaddeu Calil de (2016)
The existence of life sentence in prison in the Italian judicial system does not scare judicial officials, that is why the Italian Constitutional Court has declared its constitutional legitimacy, highlighting it's perpetual character. Life sentence has therefore been considered 'emptied' and humanised because of the existence of several benefits that are given to people serving life sentences, is this the truth? In reality, life imprisonment makes it difficult for the prisoner to be rehabilitated, and in modern prisons the prisoners dignity which should be protected by the italian constitution does not seem to be respected by the organs of the European Union and international legislation.